Bone Hollow - Ventrella, Kim (New York : Scholastic Press, 2019)
Gabe was on top of his guardian's roof, trying to rescue her prize chicken and worrying about his dog, Ollie, when the tornado struck, and after that he was dead, though it takes some time for him to realize it; but somehow he is still tied to this world and generally only those who are close to death can actually see him (although there is a bit of a panic when he shows up at his own funeral)--and in that he discovers his new mission in "life:" helping others before they cross over into the light.
"Author of Skeleton Tree"--Dust jacket.
Keywords: Death -- Juvenile fiction; Future life -- Juvenile fiction; Orphans -- Juvenile fiction; Dogs -- Juvenile fiction; Helping behavior -- Juvenile fiction; Death -- Fiction; Future life -- Fiction; Ghosts -- Fiction; Orphans -- Fiction; Dogs -- Fiction; Helpfulness -- Fiction